2020
DOI: 10.5650/jos.ess20174
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Food Ingredients and Vegetable Oils on Thermal Isomerization of Lycopene

Abstract: such as tomato juice and puree 8, 9. However, lycopene Zisomers, such as the 5Z-and 9Z-isomers, are primarily found in animals and humans 8, 10, 11. A reason for the lycopene Z-isomer abundance in the body is thought to be the Z-isomerization during digestion and absorption 12 14. Re et al. reported that all-E-lycopene isomerized into the Zisomers in the human gastric juice and the 5Z-and 9Z-isomer ratios markedly increased 13. Recently, Huang and Hui found that the Z-isomerization site of all-E-lycopene was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This was supported by the low total cholesterol and LDL cholesterol levels in experimental human subjects consuming tomato juice with olive oil in a randomized control trial (Arranz et al., 2015). It is noteworthy to highlight that tomato lycopene, when reacted with selected food ingredients and vegetable oils such as garlic, broccoli, and olive oil, could undergo thermal Z‐isomerization (Honda et al., 2020).…”
Section: Effect Of Food Matrix Post‐harvest Processing and Compounds ...mentioning
confidence: 99%
“…This was supported by the low total cholesterol and LDL cholesterol levels in experimental human subjects consuming tomato juice with olive oil in a randomized control trial (Arranz et al., 2015). It is noteworthy to highlight that tomato lycopene, when reacted with selected food ingredients and vegetable oils such as garlic, broccoli, and olive oil, could undergo thermal Z‐isomerization (Honda et al., 2020).…”
Section: Effect Of Food Matrix Post‐harvest Processing and Compounds ...mentioning
confidence: 99%
“…It should be noted that even well-planned nutritional concepts, the role of which is to enrich the human body with lycopene, may not be fully sufficient to compensate for this deficit. The result is its poor intestinal absorption, low bioavailability, and decreased liver capacity by incorporating lycopene into lipoprotein carriers [118]. Therefore, the development of new lycopene supplements with increased bioavailability is of great importance in the light of modern nutritional science.…”
Section: Lycopene Supplementation and The Risk Of Cardiovascular Dise...mentioning
confidence: 99%
“…However, a majority of these previous studies used highly toxic heavy metal catalysts, such as iron (III) chloride, copper (II) chloride, and titanium tetrachloride 43, 60−62) . In recent studies conducted by us, specific food ingredients were observed to possess Z-isomerization-promoting effects and the causative agents, such as isothiocyanates and polysulfides, were successfully identified 52,63,64) . Specifically, we investigated the effect of 131 food ingredients (fresh vegetables, fresh mushrooms, dried spices, and dried seaweeds) on the total Z-isomer ratio of lycopene in tomato puree containing 5% olive oil after heating at 80℃ for 1 h. The results of this test revealed that specific vegetables, such as Allium sp.…”
Section: Catalytic Treatmentmentioning
confidence: 99%